2011
DOI: 10.3329/ptcb.v21i2.10242
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fingerprinting and Diversity Analysis of BRRI Hybrid Varieties and their Corresponding Parents

Abstract: DNA fingerprinting and genetic diversity of four Bangladesh Rice Research Institute (BRRI) hybrid varieties and their parental lines were carried out. A total of 73 microsatellite markers were tested for screening the genotypes. Among the 73 amplified products, 37% had polymorphic bands showing 81 alleles. The number of alleles per locus ranged from two (RM10) to eight (RM327), where average allele number was 4.333. The Polymorphism Information Contents (PIC) lied between 0.337 (RM10) and 0.852 (RM327). RM327 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…In the present study higher PIC values (varied from 0.76 to 0.94) were observed than the earlier works [17][18] but are quite comparable to other studies [19][20][21]. High PIC values can be due to the fact that rice accessions used in this study were collected from diverse regions of Bangladesh so that more variability might exist in such population.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study higher PIC values (varied from 0.76 to 0.94) were observed than the earlier works [17][18] but are quite comparable to other studies [19][20][21]. High PIC values can be due to the fact that rice accessions used in this study were collected from diverse regions of Bangladesh so that more variability might exist in such population.…”
Section: Discussionsupporting
confidence: 58%
“…Morphological characterization has been efficient until now for identifying genetic material; however, this method has become inefficient for differentiation of commercial varieties (Rahman et al, 2009) because of the greater uniformity in morphological traits of the commercial varieties and the low number of morphological traits available (Rahman et al, 2009;2010;Islam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Simple sequence repeat (SSR) markers have been widely used in genetic diversity studies and to identify rice varieties (McCouch et al, 2002;Garris et al, 2004;Lu et al, 2005;Chuang et al, 2011;Islam et al, 2011;Kanawapee et al, 2011). In rice, genomic SSRs form part of coding or noncoding regions of the genome (Varshney et al, 2005) and they are also called neutral or anonymous because they do not consider the degree of phenotypic expression of the sequences (Gupta and Rustgi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…All these findings indicated that the rice accessions used in the present study had a broad genetic diversity. The average PIC values reported were 0.57 (Ravi et al 2003), 0.57 (Zeng 2004), 0.66 (Zhao et al 2009), 0.46 (Seetharam et al 2009), 0.53 (Pervaiz et al 2010), 0.603 (Islam et al 2011), 0.57 (Shamim et al 2015), 0.665 (Yadav et al 2015), and 0.47 (Anh et al 2018), respectively. These values were comparatively higher than the earlier reports, which might be due to the high diversity of rice accessions used in their studies or the use of highly polymorphic markers.…”
Section: Resultsmentioning
confidence: 98%
“…A range of 2-4 alleles per locus was reported (Gour et al 2017; Ming et al 2015; Mvuyekure et al 2018; Verma et al 2019). The average number of alleles was 6.72 (Ravi et al 2003), 4.90 (Zeng 2004), 4.50 (Pervaiz et al 2010), 8.00 (Zhao et al 2009), 4.30 (Islam et al 2011), 7.40 (Shamim et al 2015) and 6.40 (Watanabe et al 2016), which might be due to the use of a more diverse set of rice accessions in their study or due to the use of highly polymorphic markers.…”
Section: Resultsmentioning
confidence: 99%